Peranan Metode Scientific Crime Investigation Melalui Ilmu Kedokteran Forensik Dalam Proses Pengungkapan Jenazah di Pondok Gede Permai, Kota Bekasi - Ratu Wida Widyaningsih Suhandi; Handar Subhandi Bakhtiar (Jurnal Hukum dan Sosial Politik, 2024)
Forensics is the science of scientifically proving evidence found at a crime scene. Forensic medicine, also known as Legal Medicine/Forensic Medicine, is one of the specialised branches of medical science for the purposes of law enforcement and justice (judicial and non-judicial). Normative legal research or library research, with a statutory approach, conceptual approach, comparative approach, and historical approach. The nature of the research used in this research is descriptive-prescriptive, the author uses content analysis. The results of this study The process of proof is an activity that means an attempt to prove something (the object being proven) through evidence that can be used in certain ways to declare what is proven as proven or not according to the law. This forensic medical science is one of the vital references for law enforcement officials in revealing the facts of criminal offences that occur against victims into the light.